2013
DOI: 10.1108/tqm-11-2012-0092
|View full text |Cite
|
Sign up to set email alerts
|

The influence of airline service quality on passenger satisfaction and loyalty

Abstract: Purpose – The general objective of this study was to examine the influence of airline service quality on passenger satisfaction and loyalty. To achieve this, the research was guided by four specific objectives to which data collection was effected mainly by interview method using fully structured questionnaires. Design/methodology/approach – The study used random sampling technique and it covered 303 respondents on international flights using Entebbe International Airport. Data were analyzed using statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(161 citation statements)
references
References 19 publications
3
102
1
9
Order By: Relevance
“…Park and colleagues [42] found that three factors of SQ (service value, passenger satisfaction, and airline image) have a significant effect on the BI of passengers. Moreover, Namukasa [38] emphasized that SQ, including pre-flight, in-flight, and post-flight services, has a positive influence on CS.…”
Section: Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Park and colleagues [42] found that three factors of SQ (service value, passenger satisfaction, and airline image) have a significant effect on the BI of passengers. Moreover, Namukasa [38] emphasized that SQ, including pre-flight, in-flight, and post-flight services, has a positive influence on CS.…”
Section: Service Qualitymentioning
confidence: 99%
“…Many studies have investigated the effects of SQ on consumer behaviors, such as CS, customer loyalty, and behavioral intentions, as well as on firm performance, in various service industries [14,[37][38][39] and found it to have a positive impact [37,40]. Lee and Cunningham [37] indicated that service quality perceptions have a positive impact on service loyalty in banks and travel agencies, while Santos [12] found that high E-service quality provides long-term benefits to companies in the E-commerce industry.…”
Section: Service Qualitymentioning
confidence: 99%
“…Some researchers in their study discovered a positive effect of service quality on customer satisfaction in airline industry in various countries, such as in South Korea (Park et al, 2004), Australia (Park et al, 2005), Uganda (Namukasa, 2013), America (Baker, 2013), Nigeria (Geraldine and David, 2013), and United Arab Emirates (Hussain, 2016). Based on the theory and previous research, the hypothesis to be tested in this study is as follows: H1: There is a positive effect of service quality toward customer satisfaction Corporate image toward Customer satisfaction.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Parasuraman et al [14] argue that service quality is considered as results of customers' comparison between their expectation of the service and their perception after using the service. Tiernan et al [19] and Namukasa [11] used the model of SERVQUAL [14] and SERVPERF [2] to examine the impact of airline service quality on passenger satisfaction.…”
Section: Quality Of Aviation Servicementioning
confidence: 99%